EDUCATION VECTORS (BACK TO FUTURE) - O. V. Shchiptsov (Научный вестник МГТУ ГА, 2016)
Researcher A. Haksli has examined the school and social order in the modern world reality and ideas. The problem of teaching in university has been studied, so that this process leads to the education of creativity and independent thinking of youth. Teaching and the intellectual growth of the teacher has been reviewed. The process of training and education of young teacher and scientist has been researched. Age and teacher is the problem that should be studied.